Ketentuan dan dokumentasi hukum di pengadilan niaga dan kurator serta pengurus - [Tidak Terdaftar] (Jembar inti karya, 1999)
Ketentuan dan dokumentasi hukum di pengadilan niaga dan kurator serta penguru